The effect of granulocyte colony stimulating factor on genotoxicity in allogeneic peripheral blood stem cell transplantation donors: A prospective case-control study - Çakmaklı, Hasan Fatih; Gökçe, Hafize; Söylemez, Esma; Topçuoğlu, Pervin; Kayaaltı, Zeliha; İleri, Dilber Talia (Turkish National Pediatric Society, 2023)
Background. Every year, thousands of donors are exposed to granulocyte-colony stimulating factor (G-CSF) for stem cell mobilization in hematopoietic stem cell transplantations (HSCT). Previous studies about the genotoxicity of G-CSF were inconclusive. In this study, the genotoxic effects of G-CSF in peripheral blood stem cell (PBSC) donors were evaluated prospectively by using three different validated and reliable methods for the first time in the literature to the best of our knowledge. Methods. Donors of PBSC transplantation (n=36), who received G-CSF were evaluated for genotoxicity by micronucleus test (MNT), nuclear division index (NDI), and comet assay (CA). Genotoxic effects are expected to cause an increase in MNT and CA values and decrease in NDI. Blood samples were collected at three time-points (TP): before starting G-CSF (TP1), after G-CSF for five days (TP2), and one month after the last dose (TP3). Sixteen controls were included for baseline comparison of genotoxicity tests. CD34 cell counts and hemograms were also analyzed. Results. MNT and CA parameters; comet and tail length, tail DNA%, and tail moment, showed no change in time whereas another CA parameter, Olive’s tail moment (OTM) was increased significantly at TP3 compared to both baseline and TP2 (p=0.002 and p=0.017, respectively). Nuclear division index decreased significantly at TP2 (p[removed]
Keywords: Comet Assay; Genotoxicity Tests; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cell Donor; Hematopoietic Stem Cell Mobilization; Micronucleus Tests; Peripheral Blood Stem Cell Transplantation; Tissue Donor